2022
DOI: 10.52312/jdrs.2022.564
|View full text |Cite
|
Sign up to set email alerts
|

Indirect impact of the COVID-19 pandemic on diabetes-related lower extremity amputations: A regional study

Abstract: The outbreak of severe acute respiratory syndrome-Coronavirus 2 (SARS-CoV-2) was first began in China and led to a global novel coronavirus disease 2019 (COVID-19) pandemic in 2020. [1] As the spread of the pandemic has continued, more than a million deaths were reported due to COVID-19 infection worldwide. [2] Due to the rapid spread of the virus, healthcare systems were exposed to a large number of COVID-19 infection patients which created a potential collapse risk of healthcare systems. [3] Healthcare auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In Bangladesh, a retrospective single-center study [ 50 ] reported increased prevalence of total amputations as well as major and minor amputations during the pandemic period. In Turkey, a single single-center, retrospective study [ 51 ] reported that there was no change in the amputation incidence and levels during the pandemic period. In Israel, a retrospective study conducted at a level 2 medical center reported that there was no statistically significant difference in the mortality and major amputation rates in persons with diabetic ulcer before and during the pandemic [ 52 ].…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, a retrospective single-center study [ 50 ] reported increased prevalence of total amputations as well as major and minor amputations during the pandemic period. In Turkey, a single single-center, retrospective study [ 51 ] reported that there was no change in the amputation incidence and levels during the pandemic period. In Israel, a retrospective study conducted at a level 2 medical center reported that there was no statistically significant difference in the mortality and major amputation rates in persons with diabetic ulcer before and during the pandemic [ 52 ].…”
Section: The Indirect Impact Of the Covid-19 Pandemic On Diabetes-rel...mentioning
confidence: 99%
“…The first reports during the lockdown were limited to small cohorts of single specialized centers which showed different results [24,39,40,43,[47][48][49][50][51][52], while subsequently several complete population studies have been published [42,[44][45][46]56].…”
Section: Conclusion and Lessons Learned For Our Futurementioning
confidence: 99%
“…11,12 However, not all studies have found the same trend, with a few reporting no differences in amputation rates and two studies reporting a reduction in amputation rates during the pandemic. [12][13][14][15][16][17] The studies that reported a reduction in amputation procedures, however, reflect a shorter follow-up time of 3-4 months into the pandemic that only included the initial lockdown period of the pandemic and therefore fail to capture the intermediate to long-term effects of delayed procedures or follow-ups. 12,14 The state of Victoria had some of the strictest restrictions in Australia during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Most of the patients with chronic illnesses did not have a regular follow-up during the pandemic due to individuals’ fear of getting the virus or self-isolation regulations. [ 2 ] Patients with DM have a lifetime risk of up to 25% of developing diabetic foot; however, approximately 60 to 80% of patients’ foot ulcers heal, while 10 to 15% do not progress and 5 to 24% eventually require a limb amputation. [ 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…[1] Most of the patients with chronic illnesses did not have a regular follow-up during the pandemic due to individuals' fear of getting the virus or self-isolation regulations. [2] Patients with DM have a lifetime risk of up to 25% of developing diabetic foot; however, approximately 60 to 80% of patients' foot ulcers heal, while 10 to 15% do not progress and 5 to 24% eventually require a limb amputation. [3] Lower limb amputation (LLA) patients have a significant mortality rate, which may be due to the fact that the majority of patients are elderly and have many comorbid conditions in addition Objectives: The aim of this study was to evaluate the factors that influenced one-year and five-year mortality and to compare major and minor amputations in diabetic patients with comorbidities.Patients and methods: Between February 2008 and November 2014, a total of 201 type 2 diabetic foot patients (147 males, 54 females; median age: 65.99 years; range, 50 to 92 years) who underwent amputation were retrospectively analyzed.…”
mentioning
confidence: 99%